Gambaran Persepsi Body Image dan Status Gizi Remaja di SMA N 10 Kota Jambi - Harianja, Naomi Fasca Sari; Ariyanto, Ariyanto; Hatussaadah, Siti Fati (3031-8572, 2024)
The nutritional status of adolescents is influenced by several factors, including diet, physical activity, health conditions, genetic factors, and one of them is body image. Their beliefs and attitudes about their bodies, which are shaped by body images considered ideal by society, may affect their self-esteem. As a result, some adolescents may take actions that may affect their nutritional status. The purpose of this study was to determine the body image perceptions and nutritional status of adolescents in SMA N 10 Jambi City. This research was conducted in May-July 2024 at SMA N 10 Jambi City. This research is quantitative research. Data was collected by distributing questionnaires and measuring nutritional status. The sample size was 86 adolescents. Data analysis in this study used univariate analysis to determine the description of body image perceptions and nutritional status. The results showed that the percentage of adolescents who had a positive body image was 42 people (49.4%) and 43 people (50.6%) had negative body image perceptions. The picture of nutritional status is poor for 7 people (8.2%), good for 56 people (65.9%), overnourished for 17 people (20%) and obese for 5 people (5.9%). It can be concluded that there are still many adolescents with negative perceptions of body image and nutritional status. Therefore, it is suggested to the school to collaborate with the local health centre to provide education on body image and to monitor the nutritional status of adolescents.